2014
DOI: 10.2147/ppa.s62925
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term subjective medical treatment outcome of trauma surgery patients: the importance of physician empathy

Abstract: PurposeTo investigate accident casualties’ long-term subjective evaluation of treatment outcome 6 weeks and 12 months after discharge and its relation to the experienced surgeon’s empathy during hospital treatment after trauma in consideration of patient-, injury-, and health-related factors. The long-term results are compared to the 6-week follow-up outcomes.Patients and methodsTwo hundred and seventeen surgery patients were surveyed at 6 weeks, and 206 patients at 12 months after discharge from the trauma su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 71 publications
2
48
0
Order By: Relevance
“…Empathy can be defined as 'an ability to (i) understand the patient's situation, perspective and feelings (and their attached meanings); (ii) communicate that understanding and check its accuracy; and (iii) act on that understanding with the patient in a helpful (therapeutic) way' (20). Empathy has been shown to correlate with patient enablement (21-23), patient satisfaction (24,25) and improved health outcomes in a wide range of clinical settings (23,(26)(27)(28)(29)(30)(31). To date, research is lacking that evaluates the association of BMI and patients' experiences of weight stigma in health care with their perception of physician empathy.…”
Section: Introductionmentioning
confidence: 99%
“…Empathy can be defined as 'an ability to (i) understand the patient's situation, perspective and feelings (and their attached meanings); (ii) communicate that understanding and check its accuracy; and (iii) act on that understanding with the patient in a helpful (therapeutic) way' (20). Empathy has been shown to correlate with patient enablement (21-23), patient satisfaction (24,25) and improved health outcomes in a wide range of clinical settings (23,(26)(27)(28)(29)(30)(31). To date, research is lacking that evaluates the association of BMI and patients' experiences of weight stigma in health care with their perception of physician empathy.…”
Section: Introductionmentioning
confidence: 99%
“…When doctors demonstrate empathy, patients are less anxious (Fogarty et al, 1999), and diagnostic accuracy is improved, leading to better treatment planning and patient adherence to treatment regimen (Zolnierek, 2009;Hojat et al, 2011b). One study of surgical outcomes concluded that surgeon empathy had a significantly positive indirect effect on patient satisfaction through its relationship to patients' self-reported health status (Weng, 2011); while another study concluded that physician empathy predicted patients' perceived medical outcomes (Steinhausen et al, 2014). Other research found that patients with diabetes who perceive their physicians as empathetic have lower HA1C scores, improved low-density lipoprotein (Hojat et al,2011b), and fewer acute metabolic complications (Del Canale et al,2012), as well as improved self-management skills (Sultan et al, 2011).…”
Section: Effects Of Physician Empathy On Patientsmentioning
confidence: 99%
“…2 Humanism is a way of being defined by the characteristics of empathy, altruism, and compassion. 3 6 and improved adherence to an agreed-upon plan of care. 7 When coupled with the observations highlighting the decline of empathy among learners 8 and the missed opportunities for demonstrating empathy among practicing physicians, 9 it becomes essential for us to consciously role model and teach humanistic values to learners.…”
Section: What Is Humanism?mentioning
confidence: 99%